Poly(glycerol citrate)‐polylactide nonwovens toward tissue engineering applications. (3rd June 2021) - Wrzecionek, Michał; Bandzerewicz, Aleksandra; Dutkowska, Ewa; Dulnik, Judyta; Denis, Piotr; Gadomska‐Gajadhur, Agnieszka
Abstract: In 2002, Robert Langer proposed that new polyester for tissue engineering should have good mechanical properties followed by: covalent bonding (as crosslinking) and hydrogen‐bonding interactions; and should be elastic like rubber materials due to three‐dimensional network structure. Considering these hypotheses, a polyester made of glycerol and citric acid was designed in this work. Poly(glycerol citrate) should be attractive for tissue engineering because both glycerol and citric acid, taking part in natural human metabolic pathways; and due to the reactant's functionality, 3D networks should be produced easily. Moreover, the reagents are cheap, available, and often used in the food and pharmaceutical industries. In this work, poly(glycerol citrate) was synthesized and then used with PLA for creating porous nonwovens by electrospinning. Produced materials were tested for possible application in the field of tissue engineering. The obtained materials have properties similar to collagen fibers, but still, require refinement for medical applications.